Anthropogenic and biogenic components of carbon dioxide flux in Łódź - Pawlak , Włodzimierz; Siedlecki , Mariusz; Fortuniak , Krzysztof (Acta Geographica Lodziensia, 2024)
The eddy covariance method allows the determination of the daily, seasonal and annual vertical carbon dioxide exchange between the urban surface and the atmosphere. However, these measurements do not contain information about what processes influence the intensity and direction of this exchange. In the case of urbanized areas, the intensity of CO2 exchange is determined by both biogenic processes (as a result of the presence of urban vegetation) and processes related to human activity (e.g. human respiration and combustion of fossil fuels). The aim of this paper is to present preliminary results of determining bio- and anthropogenic components of CO2 exchange in Łódź. For this purpose, the statistical approach proposed by Menzer and McFadden for American cities was applied (Menzer, McFadden 2017). The analysis used data from 2012–2015 from the measurement site at 81 Lipowa St., located in the western part of the centre of Łódź. The results indicate that all anthropogenic components of the net CO2 flux determined for the selected part of the centre of Łódź have positive values, so they indicate emissions of this gas into the atmosphere. The most significant component of the net CO2 flux in Łódź is, regardless of the season, the flux associated with the combustion of fossil fuels in car engines. In the cold half of the year, the flux associated with residential heating also plays an important role.